2014
DOI: 10.1074/jbc.m114.580001
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Lyn Tyrosine Kinase through Decreased Membrane Cholesterol Levels during a Change in Its Membrane Distribution upon Cell Detachment

Abstract: Background: Lyn tyrosine kinase is anchored to the plasma membrane. Results: Cell detachment changes Lyn distribution from the low density to the high density membrane fractions and activates Lyn through decreased membrane cholesterol levels. Conclusion: Cell detachment-induced Lyn activation plays a role in survival of suspension cells. Significance: Our results provide novel insight into signal transduction upon cell detachment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…3) We showed that newly synthesized Lyn, a member of Src-family kinases, in the cytoplasm is biosynthetically accumulated at the Golgi, which contains various membranous cisternae and clusters of vesicles, including cis-, medial-and trans-Golgi cisternae and the trans-Golgi network (TGN), 4,5) and Golgi-associated Lyn is subsequently transported to the plasma membrane. [6][7][8][9][10] Since the localization of proteins is linked to their functions, we also showed that Golgi-associated Lyn can serve as a signaling platform under oxidative stress. 7) Although newly synthesized secretory proteins move through the secretory pathway: rough endoplasmic reticulum (ER) cis-, medial-and trans-Golgi cisternae secretory or transport vesicles plasma membrane, the intra-Golgi localization of Lyn remains elusive.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…3) We showed that newly synthesized Lyn, a member of Src-family kinases, in the cytoplasm is biosynthetically accumulated at the Golgi, which contains various membranous cisternae and clusters of vesicles, including cis-, medial-and trans-Golgi cisternae and the trans-Golgi network (TGN), 4,5) and Golgi-associated Lyn is subsequently transported to the plasma membrane. [6][7][8][9][10] Since the localization of proteins is linked to their functions, we also showed that Golgi-associated Lyn can serve as a signaling platform under oxidative stress. 7) Although newly synthesized secretory proteins move through the secretory pathway: rough endoplasmic reticulum (ER) cis-, medial-and trans-Golgi cisternae secretory or transport vesicles plasma membrane, the intra-Golgi localization of Lyn remains elusive.…”
mentioning
confidence: 93%
“…10,15) Confocal images were obtained using a Fluoview FV500 (Olympus, Japan) laser scanning microscope with a 60× water-immersion objective. The Pearson's R values were determined as described.…”
Section: )mentioning
confidence: 99%
“…Knockdown of c-Src was performed with shRNA for silencing c-Src (sh(c-Src); 5Ј-GCTCCAGATTGTCAACAAC-3Ј) (68). Knockdown of Fyn was performed with shRNA for silencing Fyn (sh(Fyn); 5Ј-GGAAGAGCTCTGAAATTAC-3Ј) (69). Knockdown of Lyn was performed with shRNA for silencing Lyn (sh(Lyn); 5Ј-GGACAGAGGTTTCAAACTA-3Ј) (69).…”
Section: Methodsmentioning
confidence: 99%
“…HeLa S3/TR cells, which can express v-Src (HeLa S3/TR/v-Src) or c-Src-HA, were prepared recently (79,80). HeLa S3/sh(Fyn) cells, HeLa S3/sh(Lyn) cells, and HeLa S3/sh(Fyn)ϩsh(Lyn) cells were generated by using pENTR4/H1/sh(Fyn) and/or pENTR4/H1/sh(Lyn) with a plasmid containing the hygromycin resistant gene as described previously (69). Cells seeded in a 35-mm (60-mm) culture dish were transiently transfected with 1 g (3 g) of plasmid DNA using 5 g (15 g) of linear polyethyleneimine (25 kDa) (Polyscience, Inc.) (78).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation